Pengaruh Transformational Leadership, Work Life Balance, dan Autonomy Terhadap Employee Engagement Karyawan Generasi Z di Perusahaan Digital - Merry Ivonni; Arop Ria Saulina Panjaitan (Masyarakat Ekonomi Syariah Bogor, 2026)
The development of the digital economy in Indonesia has driven the rapid growth of digital start-ups, which in turn has transformed the characteristics and dynamics of the workforce, particularly for Generation Z employees. A dynamic, flexible, and high-pressure work environment makes employee engagement a crucial factor in maintaining performance stability. This study aims to determine the influence of transformational leadership, work-life balance, and job autonomy on the employee engagement of Generation Z workers in digital start-up companies. A quantitative approach was employed, and data were analyzed using multiple linear regression. The sampling technique utilized a purposive sampling method, involving 164 Generation Z respondents. The results indicate that, partially, transformational leadership and job autonomy have a positive and significant effect on employee engagement. Conversely, work life balance does not have a significant effect on employee engagement. Simultaneously, transformational leadership, work life balance, and job autonomy significantly influence employee engagement. The managerial implications of this research suggest that digital start-ups need to strengthen transformational leadership practices and provide clear job autonomy to sustainably enhance employee engagement.